Synthesis of the optimum two-channel direction finder with linear scanning of the antenna pattern - M. M. Bulash; S. V. Shaliapin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Target angular coordinates two-channel measurer synthesis and the description of operational algorithm in case of use of the antenna pattern linear scanning are described. This algorithm allows to decrease fluctuations of a reflected signal pack that approximates it to instantaneous comparison methods by its accuracy characteristics.